Respon Fikih terhadap Perkembangan Teknologi Rukyat - Sakirman Sakirman (Al-Manahij: Jurnal Kajian Hukum Islam, 2020)
The method used to determine the beginning of the Islamic month which refers to the hilal regularity is called rukyat. The central issue of rukyat disruption is the problem of visual contrast of sky twilight, namely the difference in light or the color between the object and the foreground. The hilal (the new crescent moon) is dim, thin, and its color is almost the same as the sky around it so it makes the human eyes in a normal state unable to see directly the hilal without using the tools. Moreover, the technology of rukyat has developed significantly by discovering the optical technology named the rukyat telescope. However, this telescope is not able to identify hilal (the new moon), because it is only functioned to collect the light; so, when the twilight (syafak) light is strengthened, the hilal light is also equally strengthened. Furthermore, rukyat technology that is possibly used is digital imaging assisted by software that works to increase the light contrast so that the hilal can be seen by the visual eyes. Finally, digital imaging technology has an important role as a media verifier of the testimony stated by someone seeing the hilal, contrarily, its validity is doubtful. In responding to the development of technology used for finding the new crescent (rukyatulhilal), both classical and contemporary fiqh scholars give positive responses related to the use of rukyat tools that aim to facilitate the process of seeing the crescent (rukyatulhilal), especially in terms of clarifying the crescent sight object so that the new moon can be seen with the visual eye.